2007
DOI: 10.1111/j.1529-8817.2007.00390.x
|View full text |Cite
|
Sign up to set email alerts
|

Verrucophora farcimengen. et sp. nov. (Dictyochophyceae, Heterokonta)—a bloom‐forming ichthyotoxic flagellate from the Skagerrak, Norway1

Abstract: Since 1998, a heterokont flagellate initially named Chattonella aff. verruculosa has formed recurrent extensive blooms in the North Sea and the Skagerrak, causing fish mortalities. Cells were isolated from the 2001 bloom off the south coast of Norway, and monoalgal cultures were established and compared with the Chattonella verruculosa Y. Hara et Chihara reference strain NIES 670 from Japan. The cells in Norwegian cultured isolates were very variable in size and form, being large oblong (up to 34 lm long) to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
63
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(69 citation statements)
references
References 40 publications
6
63
0
Order By: Relevance
“…The marine dictyochophyte genus Pseudochattonella Eikrem, Edvardsen & Throndsen presently embraces two closely related species, Pseudochattonella verruculosa (Y. Hara & Chihara) Eikrem and Pseudochattonella farcimen Eikrem, Edvardsen & Throndsen (Edvardsen et al, 2007). They belong to the order Florenciellales together with the picoflagellate Florenciella parvula Eikrem (Edvardsen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The marine dictyochophyte genus Pseudochattonella Eikrem, Edvardsen & Throndsen presently embraces two closely related species, Pseudochattonella verruculosa (Y. Hara & Chihara) Eikrem and Pseudochattonella farcimen Eikrem, Edvardsen & Throndsen (Edvardsen et al, 2007). They belong to the order Florenciellales together with the picoflagellate Florenciella parvula Eikrem (Edvardsen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…They belong to the order Florenciellales together with the picoflagellate Florenciella parvula Eikrem (Edvardsen et al, 2007). Cells of Pseudochattonella are variable in size (5-50 mm long) and form, have two heterokont flagella, many golden brown chloroplasts and a warty appearance due to protruding mucocysts (Edvardsen et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…However, the resolution and support provided by the short 5S rDNA sequence was poor. Generally, the concatenation of 18S and 28S rDNA has improved reconstruction of the heterokont phylogeny (Ben Ali et al, 2002;Edvardsen et al, 2007;Riisberg et al, 2009). In our concatenated analysis, many of the deep branches are well supported, but there are few taxa for which data on both genes are available and this hinders any further resolution of the placement of Hydrurus, other than its allocation to the Chrysophyceae.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies of raphidophytes have successfully used the rDNA-ITS region to examine raphidophyte relationships, and there is relatively broad coverage of rDNA-ITS sequences available in public databases. These studies have shown that, while there is a variation among different species, there is little or no rDNA-ITS sequence variation within species, even among isolates from across the globe (Kooistra et al, 2001;Bowers et al, 2006;Edvardsen et al, 2007). Therefore, this region is a potentially useful means to distinguish distinct species of raphidophytes.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, 2 Chattonella species (C. globosa and C. verruculosa) have been separated from the class Raphidophyceae based on molecular analysis. They now belong to the class Dictyochophyceae and are currently regarded as a taxonomic synonym of Vicicitus globosus (Hara & Chihara) Chang and Pseudochattonella verruculosa (Hara & Chihara) HosoiTanabe, Honda, Fukaya, Inagaki & Sako (Edvardsen et al, 2007;Hosoi-Tanabe et al, 2007;Takano et al, 2007;Cheng et al, 2012). Therefore, the genus Chattonella has 5 species.…”
Section: Introductionmentioning
confidence: 99%